2012
DOI: 10.1007/s00267-012-9890-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Labile Organic Carbon Fractions and Soil Enzyme Activities after Marshland Reclamation and Restoration in the Sanjiang Plain in Northeast China

Abstract: The extensive reclamation of marshland into cropland has tremendously impacted the ecological environment of the Sanjiang Plain in northeast China. To understand the impacts of marshland reclamation and restoration on soil properties, we investigated the labile organic carbon fractions and the soil enzyme activities in an undisturbed marshland, a cultivated marshland and three marshlands that had been restored for 3, 6 and 12 years. Soil samples collected from the different management systems at a depth of 0-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 46 publications
6
33
0
Order By: Relevance
“…Notably, the highly labile organic carbon content was not associated with an increase in the carbon cycle-related enzyme activities. However, the opposite relationship between the soil labile organic carbon and the activities of invertase and b-glucosidase was observed by Song et al (2012), and this may be due to a decrease in the efficiency of soil microbial decomposition under high-intensity thinning. The final products of invertase and b-glucosidase are glucose and fructose, which are labile carbon and energy sources for microorganisms (Frankenberger and Johanson, 1983;Esen, 1993).…”
Section: Soil Enzyme Activitiesmentioning
confidence: 81%
“…Notably, the highly labile organic carbon content was not associated with an increase in the carbon cycle-related enzyme activities. However, the opposite relationship between the soil labile organic carbon and the activities of invertase and b-glucosidase was observed by Song et al (2012), and this may be due to a decrease in the efficiency of soil microbial decomposition under high-intensity thinning. The final products of invertase and b-glucosidase are glucose and fructose, which are labile carbon and energy sources for microorganisms (Frankenberger and Johanson, 1983;Esen, 1993).…”
Section: Soil Enzyme Activitiesmentioning
confidence: 81%
“…The activity of cellobiohydrolase (CBH), β-1,4-glucosidase (βG), α-1,4-glucosidase (αG), β-xylosidase (βX), β-1,4-N-acetylglucosaminidase (NAG), acid (alkaline) phosphatase (AP), and urease (UA) regulates the discharge of bioavailable nutrients from organic carbon (C), nitrogen (N), and phosphorus (P) [1012] and often benefits from addition of organic materials [13]. Absolute enzyme activity and its stability in soil are also influenced by soil pH, nutrients, microbial biomass, C pool, and microbial community composition [1415]; all these factors, in turn, are influenced by organic matter, nutrients, and microbes in CS. However, if applied in excess, CS can also lower soil quality and productivity [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effect of land use changes can be assessed using microbial community metrics such as bacterial community structure and composition [10,11], enzymatic activity [12][13][14], and soil organic carbon [15][16][17][18]. Researchers have tied the status of Soil Organic Carbon (SOC) to the activity of soil enzymes [19,20], including phosphatases [14]. It has even been suggested that these properties be used as indicators of change in wetland systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have tied the status of Soil Organic Carbon (SOC) to the activity of soil enzymes [19,20], including phosphatases [14]. It has even been suggested that these properties be used as indicators of change in wetland systems [20]. Erosion, incomplete mineralization of organic matter, and anoxia are all characteristics of wetlands that have the potential to impact the structure and function of microbial communities.…”
Section: Introductionmentioning
confidence: 99%